DETERMINANT FACTORS OF GENETIC MISCONCEPTION AT 12th GRADE SENIOR HIGH SCHOOL STUDENT IN SAMPANG - Nufus, Hayatin; Prastiwi, Muji Sri (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
Twelfth grade senior high school students potentially have misconceptions in genetic material. The characteristics of genetic material are difficult to sense and complex, difficult to understand, and have the potential to cause misconceptions. Misconceptions can be caused by student factors, textbooks, contexts, teachers, and learning methods. This study aims to describe the categories of genetic misconceptions in students, to determine the determinant factors that cause the students' genetic misconceptions, and to give solutions in reducing or preventing the genetic misconceptions in students. The research used a mixed-method with sequential explanatory with multiple linear regression analysis on 58 samples of 12th-grade high school students in Sampang. The results of this study were categorization of students' genetic misconceptions percentage from low: moderate: high misconception, were 27.59%: 41.38%: 31.03%. Based on the high and medium categorization of students who have genetic misconceptions, 17.9% of the misconceptions were caused by student factors and learning methods. Student factor (X1) has a significant positive effect on students' genetic misconceptions (Y) with the t value of 2.590. The contribution of students and learning methods to student misconceptions can be written with the equation Misconception = 51.285 + 0.268 Student - 0.256M.Learning. The solution to minimize students' genetic misconceptions is through clinical learning by conducting a misconception test and continued with the 5e learning cycle model learning such as engagement, exploration, explanation, elaboration, and evaluation. The implication of this study is teacher can strategize minimizing student factor in genetic misconception, such as through learning activity in the class. Keyword: determinant factor, misconception, student’s factor, learning method factor, 5e learning